Future energy networks and the role of interactive gaming as simulation. (August 2016) - Barrios-O'Neill, Danielle; Hook, Alan
Highlights: As simulations of complex systems, interactive games have considerable potential to be helpful in engaging consumers in sustainable energy practices. There are numerous practical ways for energy-related games to link with data in the real world, especially within the emerging Internet of Things. Game simulation is becoming instrumental toward the longer-term goal of cultivating more complex patterns of interaction and cultural analysis around energy use. Abstract: As energy systems integration deepens to support the development of a cleaner and more intelligent energy infrastructure, it will be increasingly important for consumers to better understand their relationship to energy systems and to take more proactive roles in managing energy. Foregrounding the importance of systems comprehension, we argue for the strong potential of interactive games to be helpful in engaging consumers in sustainable energy practices, as they can demonstrate complex system dynamics through simulation-based experiences. Focusing on interrogations of engagement and social change posed by gaming theorists and designers, and using several flagship interactive games as points of reference, we discuss the elements of game space that make it capable of simulating complex systems and large-scale implications of energy decisions richly and effectively. We discuss social, technological, and narrative elements of game play, pairing a theoretical investigation with a practical exploration of how energy related games can link with data in the real world, with particular emphasis on the emerging Internet of Things. Our conclusions emphasise the importance of game simulation toward the longer-term goal of cultivating more complex patterns of interaction and cultural analysis around energy use; this is based on the assertion that energy, a social resource, must be managed in ways that are equally social.